2020
DOI: 10.1108/jic-11-2019-0257
|View full text |Cite
|
Sign up to set email alerts
|

The model of distribution of human and machine labor at intellectual production in industry 4.0

Abstract: PurposeThe purpose of the paper is to develop a model of distribution of human and machine labor at intellectual production in Industry 4.0.Design/methodology/approachThe basis of the methodology of the research is regression analysis. The analyzed variables are independent variables that characterize the level of development of human and machine labor in the economy of a country; dependent variables that reflect the effectiveness of the production, marketing and innovative business processes in the economy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 27 publications
(26 reference statements)
1
17
0
1
Order By: Relevance
“…It is necessary to note here that the science of civil procedural law draws attention to the importance of digital transformation of justice (Dudin et al, 2019;Inshakova et al, 2020;Kalinina et al, 2019;Rusakova et al, 2020). Thus, we can agree with the statement of Valeev and Nuriev (2019) about the lack of clear "indicators" of the development of economic justice in the context of digitalization.…”
Section: Research Questionssupporting
confidence: 59%
“…It is necessary to note here that the science of civil procedural law draws attention to the importance of digital transformation of justice (Dudin et al, 2019;Inshakova et al, 2020;Kalinina et al, 2019;Rusakova et al, 2020). Thus, we can agree with the statement of Valeev and Nuriev (2019) about the lack of clear "indicators" of the development of economic justice in the context of digitalization.…”
Section: Research Questionssupporting
confidence: 59%
“…The evolution of the human–machine integration that allows benefiting from the different information processing capabilities of both parties has been investigated in this context in a comprehensive manner [ 5 ]. Extensive and intensive research has shown that on the one hand, humans in shop-floor management environments in I4.0, have a holistic problem-solving capability where several brain areas are activated for problem solving [ 44 , 45 , 46 ], however humans have a limit to the cognitive load they can compute that affects their performance [ 47 , 48 ]. On the other hand, with the advent of artificial intelligence, machines are increasingly capable of performing a massive processing of information that can make up for human deficiencies: one approach is to use the machine, having greater computational capacity to reduce the cognitive load of humans [ 49 , 50 , 51 ], another approach has been to create a semantic framework that allows for machine recommendations for human problem-solving related to manufacturing tasks [ 52 , 53 ], while other scholars have proposed an open source web-based protocol to enhance inter-operability between human and machine assets [ 54 ].…”
Section: State Of the Artmentioning
confidence: 99%
“…For example, globalisation makes it possible for more efficient foreign companies to 'steal' a market from domestic companies (Lopes et al 2021). Researchers have indicated that in order to meet such challenges, Polish businesses must be technologically and financially prepared (Vlčková et al 2019) because the effectiveness of businesses depends on intense application of mechanical and human labour, especially in production where applications of machine labour are the most widespread (Inshakova et al 2020). Strategies and processes that reduce operating costs (Genovese et al 2014), however, must also be intelligent (Leitao et al 2016) and autonomous (Bechtold et al 2014), which means they must involve sustainable and renewable energy (Tesch da Silva et al 2020).…”
Section: Introductionmentioning
confidence: 99%